Ancaman dan Faktor-Faktor yang Mendorong Swedia Bergabung dengan NATO pada Tahun 2024 - Aji Irvan Saputra; Indrawati Indrawati (Jurnal Ilmu Sosial dan Ilmu Politik)
Sweden maintained its neutrality in response to its history, including during the Napoleonic wars, by adopting “neutrality” as its official policy in 1834. This neutrality was upheld during both World Wars to protect trade interests. During the Cold War, Sweden chose the path of peaceful diplomacy and rejected military alliances. But Sweden experienced concerns over the Russia-Ukraine conflict and Russia's intervention in Crimea. In May 2022, Sweden eventually applied for NATO membership in response to Russia's invasion of Ukraine in February 2022. This research aims to understand the reasons behind Sweden's decision to join NATO. The factors behind Sweden's decision to join NATO are analyzed using qualitative research methods and through the lens of Threat Perception concept. This research discusses the factors behind Sweden’s decision to join NATO through five dimensions from the Threat Perception concept: structural, geopolitical, historical, socio-cultural, and economic. This research indicates that these five dimensions influenced Sweden's decision to join NATO. Firstly, Swedish ministers and political parties in Sweden played a role in the decision-making process. Secondly, Sweden's geographical location and the rising activities in the Baltic Sea also influenced its decision. Thirdly, Sweden's historical relationship with NATO compared to its relationship with Russia also influenced the decision. Fourthly, the ethnic, cultural, and religious composition of people in Sweden, along with policymaker adoption, are believed to have played a significant role in Sweden's foreign policy formation. Finally, the economic benefits of joining NATO were also considered by Sweden.